PENGARUH HABITAT DAN KETINGGIAN TEMPAT TERHADAP SEBARAN KELELAWAR DI TAMAN NASIONAL GUNUNG CIREMAI, JAWA BARAT - Maharadatunkamsi, Maharadatunkamsi (Perhimpunan Biologi Indonesia, 2012)
Effect of habitat and altitudinal changes on the distribution of bats in Gunung Ciremai National Park, West Jawa. We investigated the bat community in its density and diversity between primary forest, secondary forest, shrub and pines in Gunung Ciremai National Park. This paper discuss the impact of these nature changes on the bat community along this national park. Our data showed a relationship between distribution of each bat species with habitat changes andaltitudinal gradients between 500-600 and 1100-2100 m above sea level. The distribution of bats according to their habitat and altitude in this study is parallel with some other previous studies. The results indicated that both habitat and altitidinal differences are important factors in influencing the distribution of each bat species. Although forest and disturbed areas provide food and shelter for support many of these bats species, it is urgent to maintain and improve the quality of the forests in this important national park.Keywords: Gunung Ciremai, bats, forests, disturbed areas, altitudinal.